SEMANGAT BUSHIDO DALAM NOVEL “MUSASHI” KARYA EIJI YOSHIKAWA (SEBUAH KAJIAN BUDAYA BERDASARKAN PENDEKATAN ANALISIS ISI) - Haryono Haryono (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
Abstract. The Spirit of Bushido in “Musashi” novel by Eiji Yoshikawa. The present research deals with the Japanese cultural values that described in the novel "Musashi" written by Eiji Yoshikawa. The objective of the research was to identify the Japanese cultural values and give usefullnes in digging superior values that can be applied in everyday life. With a content analysis approach, the Japanese cultural values can be expressed in a comprehensive manner. The results of the research are identification of the Japanese cultural values and can be used as a reference for the development of Indonesian cultural values.